Low-complexity Noncoherent Iterative CPM Demodulator for FH Communication - Y. Wang; A. Liu; D. Guo; X. Liu (Radioengineering, 2013)
In this paper, we investigate the noncoherent iterative demodulation of coded continuous phase modulation (CPM) in frequency hopped (FH) systems. In this field, one important problem is that the complexity of the optimal demodulator is prohibitive unless the number of symbols per hop duration is very small. To solve this problem, we propose a novel demodulator, which reduces the complexity by applying phase quantization and exploiting the phase rotational invariance property of CPM signals. As shown by computational complexity analysis and numerical results, the proposed demodulator approaches the performance of the optimal demodulator, and provides considerable performance improvement over the existing solutions with the same computational complexity.